Assessing the Impact of Mobile Applications on Student Engagement in ICT and Computer Science Education - Ibrahim, Umar (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This study investigates the impact of mobile applications on student engagement in the realms of Information and Communication Technology (ICT) and Computer Science Education. As the integration of mobile applications in educational settings becomes increasingly prevalent, understanding their influence on student engagement is crucial for optimizing learning experiences. The study employs assess the effectiveness of selected mobile applications aligned with the curriculum. Data analysis focuses on measuring and evaluating student engagement levels. The results reveal shedding light on the implications for enhancing ICT and computer science education. This research contributes to the existing literature by addressing gaps and providing insights into the practical use of mobile applications in educational settings.